Pharmacophore Analysis of Moringa oleifera Seeds Constituent as Anti-diabetic Properties - Ardy Mursyid, Romli; Mohd. Razip, Asaruddin; Radhakrishnan, Sam Ezekiel; Mohammad Farhan Ariffeen, Rosli; Tiara Nales, Nyawai (Transactions on Science and Technology, 2017)
Pharmacophore modeling approach is a computer-aided drug design (CADD) method which possessed potential as the most promising candidates to focus on the experimental efforts in modern medicinal chemistry. M. oleifera, a well known traditional medicine used for many natural therapeutic such as treatment of inflammation, headache and to combat vitamin deficiency. One of the most important properties that found in M. oleifera seeds is antidiabetic which can prevent from rising of blood sugar level in the body. By using ligand-based pharmacophore Modelling approach, four of established diabetic medicined which is (glibenclamide), (Metformin), (Repaglinide) and (nateglinide) from published literature and database (traning set) used to generate the pharmacophore modelling using Ligandscout 4.1 computer software along with the seeds constituent (test set) to determines the closest proximity.The selected seeds contituent are (4-(-l-rhamnopyranosyloxy)benzyl isothiocyanate), (4-(4¢-o-acetyl-a-l-rhamnopyranosyloxy) benzyl isothio- cyanate), (4-(α-L-rhamnopyranosyloxy ) benzyl glucosinolate a), (niazimicin), (pterygospermin), (quecertin) and (kaempferol). Result shown the best constituent which is 4-(α-L-rhamnopyranosyloxy) benzyl glucosinolate and 4-(4-oacetyl-a-l-rhamnopyranosyloxy) benzyl isothiocyanate show anti diabetic properties.